Association between Dietary Inflammatory Index Scores and Diabetes Sensorimotor Polyneuropathy in Patients with Type 2 Diabetes Mellitus: A Case-Control Study. (21st April 2022) - Asadi, Sara; Aminianfar, Azadeh; Shiva, Fahimeh; Asadi, Sasan; Yarizadeh, Habib; Qorbani, Mostafa; Mirzaei, Khadijeh
Abstract : Background . Diabetes sensorimotor polyneuropathy (DSPN) is a common complication of diabetes. Diet has been previously related to DSPN. However, no studies have investigated the relationship between the inflammatory potential of the whole diet and DSPN. So, we aimed to examine the association between dietary inflammatory index (DII) and DSPN in Iranian adults. Methods . A total of 185 subjects with DSPN and 185 sex- and age-matched controls were selected in this case-control study. A 168-item validated food frequency questionnaire (FFQ) was used to assay dietary intakes. DII was calculated based on the developed formula. The Toronto clinical neuropathy score was applied to define DSPN. Binary logistic regression was used to estimate the odds ratios (ORs) and 95% confidence intervals (95% CIs) of DII in relation to DSPN. Results . Mean values of age and BMI for all the participants were reported as 50.79 and 28.60, respectively. Also, the median (IQR) of DII for all the participants was estimated as −0.091 (−0.93, 1.07). Our findings suggest that participants in the highest quartile of the DII had higher odds of DSPN (OR = 1.76; 95% CI: 1.03, 3.36) (p -trend = 0.01) compared to subjects in the lowest quartile of DII scores after adjustment for age and sex. Additionally, a strong association was observed after adjusting for energy intake, physical activity, education, smoking status, economic status, marital status, job, BMI, and WC in model 2 (OR = 2.23, 95% CI = 1.13–4.39) (p -trend = 0.0048). Conclusion . Higher DII score was associated with an increased risk of DSPN. Therefore, it is possible that a diet rich in anti-inflammatory nutrients and foods could improve and prevent DSPN.